Analysis of Risk Factors for Transport of Food in Refrigerated Containers within the Supply Chain - Wlodzimierz ROSOCHACKI; Ludmila FILINA-DAWIDOWICZ (Communications of International Proceedings, 2021)
Supply chain risk management forms an important issue in planning and implementing of food transport. It aims primarily at limitation of potential losses that such a chain can generate. Undertaking specific actions to limit negative consequences needs, among others, identifying risk factors relevant for the sustainable supply chain, and evaluation of possible influence. The main purpose of the article is to identify risk factors associated with food supply chains and assess their impact on risk level. The analysis covers the part of the chain that include container loading with perishable food, its road transport and handling at seaport. The case study methodology and focus group approach was used to examine risk factors. 20 risk factors were identified, which could have a potential impact on the level of risk associated with the transport of cargo in refrigerated containers. For the first time the quantitative assessment of their impact was implemented. Data on the probability of their occurrence and related consequences were obtained by means of Polish experts’ estimates. That allowed to create the ranking of the examined factors and develop the risk maps for chilled and frozen cargo. The differences in risk factors assessments for chilled and frozen cargo were noted.
Keywords: Risk Analysis; Supply Chain Management; Refrigerated Container; Perishable Food Product; Transport Infrastructure.